Perencanaan Overlay Pada Perkerasan Fleksibel Pavement di Jalan Patimura Samarinda Seberang - Zony Yulfadli (Department of Architecture, Faculty of Engineering, 2017)
ABSTRACTPavement performance is a function of the relative ability of the pavement to serve traffic in a given period. The purpose of this study to find the value of subgrade bearing capacity, the carrying capacity of the aggregate base course, the stability of the rest of the old asphalt layer, the trajectory of the average daily start and end.Methodology of calculation of thick layers of flexible pavement highways using component analysis method SNI 03-1732-1989. The calculation and analysis of flexible pavement layer thickness for overlay work in 2010 with a thickness of 4.00 cm, while the five years to come, namely in 2015 carried out by construction ACWC with 5.00 cm thick. Key-words : Component Analysis, JalanPattimura, SamarindaSeberang. ABSTRACTKinerja perkerasan adalahmerupakanfungsidarikemampuanrelativedariperkerasanuntukmelayanilalulintasdalamsuatuperiodetertentu. Tujaunpenelitianiniuntukmencarinilaidayadukungtanahdasar, dayadukung lapis pondasiagregat, stabilitassisa lapis aspal lama, lintasanharian rata-rata awaldanakhir.Metodologiperhitungantebal lapis perkerasaanlenturjalanrayadenganmenggunakanmetodeanalisakomponen SNI 03-1732-1989.Hasilperhitungandananalisatebal lapis perkerasanlenturuntukpekerjaanoverlaytahun 2010 dengantebal 4,00 cm, sedangkan lima tahun yang akan dating yaitupadatahun 2015 dilakukandengankonstruksiacwcdengantebal 5,00 cm. Kata Kunci :AnalisaKomponen, JalanPatimura, SamarindaSeberang.